Conductive‐noise suppression control improved by synchronous compensation for switching. Issue 1 (13th February 2022) - Hanioka, Shota; Iezawa, Masahiro; Ogasawara, Satoshi; Takemoto, Masatsugu; Orikawa, Koji; Ohara, Shunsuke
Abstract: In noise suppression control that switches between two inverters with opposite phases, the synchronization accuracy of switching limits the noise reduction and bandwidth. To improve the noise suppression control, this paper proposes a control method that detects the rise and fall of the inverter output voltage and compensates for the synchronization error between two inverters. The effectiveness of the proposed method was verified by applying it to the double‐three‐phase motor drive system; the synchronization error was reduced to 10 ns.